PUBLIC OPINION ON THE PEACEFUL NUCLEAR EXPLOSIONS IN THE PERM TERRITORY - S. A. Zelentsova; G. V. Arkhangelskaya; I. A. Zykova (Радиационная гигиена)
The evaluation of public opinion on radiation hazard due to consequences of peaceful nuclear explosions “Taiga” in the Perm Territory is being done on the basis of results of polls done among the population opinion leading representative social groups. Respondents know about the peaceful nuclear explosions conducted near the place of their residence many years ago. Radiation hazard for health and level of territory contamination due to these explosions are estimated by them as sufficiently high. Rumors are the first main source of information about explosions for the population of the Perm Territory. Articles on the consequences of explosions published in the mass media are sporadic and contain unbiased information together with unverified information about serious consequences of explosions for the population health.